Successful Repair Management for Urinary Bladder Perforation During Myomectomy on Cervical Myoma on Patients with Previous Cesarean Section: A Challenging Case Report - Indra Adi Susianto; Ferry Santoso; Iwan Prasetyo; Diana Novitasari; Dimas Sindhu Wibisono; Jerry Ferdinand Haposan Saragih (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2023)
The 20-25% incidence of uterine myoma often experienced by women in childbearing age and 2% of these uterine myomas attach and grow in the uterine cervical area. The chief complain of cervical myom are lumps in the lower abdomen that are getting bigger and pressing on the urinary bladder cause difficulty in urinating and are accompanied by bloody urine, although the amount of menstrual blood is still within reasonable limits. Like uterine myomas, cervical myomas are not fused with the myometrial lining but are covered by thin connective tissue on the surface.The procedure of cervical myoma based on ACOG (American College of Obstetrics and Gynecology) is hysterectomy if the patient no longer wants to get pregnant, or myomectomy if the patient still wants to have children. Both of these actions have a very high risk in which vascularization in the pelvic area will be very complex, pressure on cervical myoma will have a high risk of injuring the urinary bladder mucosa and when setting aside the lower segment of the uterus there is a risk of injury. We present a 38-year-old woman with 30x 26 x 22 cm giant cervical myoma and secondary infertility that was treated with challenging laparotomi myomectomy in colaboration with urologist to preserve fertility. There was a tear in the upper part of the urinary bladder which was elongated with irregular edges measuring 12 x 5 cm after enucleation cervical myoma. The tear was repaired immediately and there are no complications in the form of vesico-vaginal fistulas or vesico-cervical postoperatively. Penanganan Komplikasi Perforasi Vesika Urinaria saat tindakan Miomektomi pada Mioma Servikal pada Pasien Bekas Seksio Sesaria: Sebuah Laporan KasusAbstrak20-25% insiden neoplasma jinak ini sering dialami oleh wanita terjadi pada wanita usia subur dan 2% nya melekat dan tumbuh pada area servik uteri. Meskipun jumlah darah menstruasi masih dalam batas wajar, tapi keluhan dari mioma uteri yang melekat pada servik adalah benjolan pada perut bawah yang semakin membesar dan menekan pada vesika urinaria sehingga menyebabkan kesulitan berkemih. Menurut American Collage of Obstetric and Gynecology tindakan miomektomi apabila pasien masih ingin mempunyai keturunan. Meskipun resiko yang sangat tinggi karena vaskularisasi area pelvis sangat kompleks, tindakan inijuga beresiko mencederai mukosa vesika urinaria dan resiko cedera pada ureter tunnel. Tulisan ini merupakan kasus seorang wanita berusia 38 tahun dengan mioma serviks permagna berukuran 30 x 26 x 22 cm dengan infertilitas sekunder yang dilakukan miomektomi secara laparotomi bersama ahli urologi. Terdapat perforasi pada vesica urinaria bagian atas memanjang dengan tepi tidak beraturan berukuran 12 x 5 cm setelah tindakan enukleasi mioma serviks. Robekan tersebut dapat diperbaiki dan tidak ada komplikasi berupa fistula vesiko- vagina atau vesiko-serviks pasca operasi.Kata kunci: Perforasi Kandung Kemih, Miomektomi, Mioma Serviks, Infertilitas Sekunder